Використання JIRA для організації управління охороною праці на підприємстві - Лаптєв, О. М. (ХНУРЕ, 2021)
In given work was proposed to use the technology of kanban boards for the management of occupational safety at the organization. The expediency of such an approach is substantiated on the example of using the JIRA product for project management. Considered the effect in the management of work safety and production risks, which gives the use of this technology.
Keywords: охорона праці на підприємстві; JIRA